Implementation of the Village Financial System (Siskeudes) to Improve Village Financial Management Accountability - Nurul Fauziah; Sigit Hermawan (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to implement the Village Financial System (Siskeudes) to Increase Accountability of Village Financial Management (Study in Connectrejo Village Kec. Sukodono Kab. Sidoarjo). The approach used in this study is a qualitative approach as a method that will provide an overview of the Implementation of the Village Financial System (Siskeudes) to Increase Accountability of Village Financial Management. This research was conducted in the village of Tutuprejo sub-district Sukodono Kab. Sidoarjo. Connectrejo Village is one of the villages in Sidoarjo Regency that has implemented the Village Financial System application since 2016. In this study, there were several informants including the Village Head, Village Treasurer and Village Secretary in the Tutuprejo village in Sukodono District, besides that the researchers also involved other parties who outside the village of Tutuprejo, Sukodono Sub-district, namely the Accounting Lecturer of FBHIS UMSIDA who takes the Village, District, and BUMDes Accounting courses due to strengthen the results of interviews that have been carried out by researchers. The results of this study indicate that the process of using the Village Financial System (Siskeudes) application in Connectrejo Village has been running well. The stages of managing the village financial system starting from the process of inputting planning documents, budgeting, administration, accountability and reporting have been well structured in accordance with Permendagri No. 20 of 2018. The quality of village financial accountability in Connectrejo Village after using the Siskeudes application has brought good changes, including making it easier for the Connectrejo Village Government in the process of reporting village financial accountability, producing accountable financial reports and in accordance with applicable rules and regulations.